2017
DOI: 10.3389/fpsyg.2017.00622
|View full text |Cite
|
Sign up to set email alerts
|

Factor Analysis of the Brazilian Version of UPPS Impulsive Behavior Scale

Abstract: Objective: To examine the internal consistency and factor structure of the Brazilian adaptation of the UPPS Impulsive Behavior Scale.Methods: UPPS is a self-report scale composed by 40 items assessing four factors of impulsivity: (a) urgency, (b) lack of premeditation; (c) lack of perseverance; (d) sensation seeking. In the present study 384 participants (278 women and 106 men), who were recruited from schools, universities, leisure centers and workplaces fulfilled the UPPS scale. An exploratory factor analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
(31 reference statements)
0
13
0
2
Order By: Relevance
“…The items from the SUPPS-P ( Cyders et al, 2014 ) in Portuguese pertaining to all impulsiveness domains except Positive Urgency were obtained from the research team that adapted the UPPS for use in Brazil, which was shown to display adequate psychometric properties ( Nogueira et al, 2013 ; Sediyama et al, 2017 ). These researchers also provided translations of the Positive Urgency items, which are currently under validation.…”
Section: Methodsmentioning
confidence: 99%
“…The items from the SUPPS-P ( Cyders et al, 2014 ) in Portuguese pertaining to all impulsiveness domains except Positive Urgency were obtained from the research team that adapted the UPPS for use in Brazil, which was shown to display adequate psychometric properties ( Nogueira et al, 2013 ; Sediyama et al, 2017 ). These researchers also provided translations of the Positive Urgency items, which are currently under validation.…”
Section: Methodsmentioning
confidence: 99%
“…The UPPS-P Impulsive Behavior Scale consists of 59 statements rated on a 1 to 4 Likert-type scale from “agree strongly” to “disagree strongly.” The UPPS-P questionnaire has been translated into more than 10 languages, including French [ 36 ], German [ 37 ], Italian [ 38 ], Spanish [ 39 ], Korean [ 40 ], Polish [ 41 ], Portuguese [ 42 ], and Dutch [ 43 ] and multiple short forms have been developed in Arabic [ 44 ], English [ 45 ], Farsi [ 46 ], French [ 47 ], German [ 48 ], Italian [ 49 ], and Spanish [ 50 ]. A child version also has been developed and validated [ 51 ].…”
Section: Development Of the Upps-p Model Of Impulsive Personalitymentioning
confidence: 99%
“…The scale assumes a heterogeneous construct of impulsivity and comprises four dimensions: urgency, sensation seeking, (lack of) premeditation and (lack of) perseverance. The Portuguese version of the measure demonstrates adequate reliability and validity (Sediyama et al, 2017). Previous studies have demonstrated correlations of the UPPS dimensions with reward sensitivity (Carlson, Pritchard, |& Dominelli, 2013) and eating behavior (Moreno-López, Soriano-Mas, Delgado-Rico, Rio-Valle, |& Verdejo-García, 2012).…”
mentioning
confidence: 88%